Optical imaging of artificial latent fingerprints using rhodamine 6G and Au-core/Pd-shell nanorods - Kitsakorn Locharoenrat; Pattareeya Damrongsak (My University, 2019)
Latent fingerprints represent valuable information-storage platforms, which play a key role in the forensic practice and health assessment.Recent works have explored novel image-enhancement methods in latent fingerprinting, which are associated with fluorescence dyes.In this study we improve the quality of fingerprint images, using a combination of fluorescence dyes and bimetallic nanoparticles.We find that Rhodamine 6G can serve as a kind of 'glue' adhering well onto Au-Pd core-shell nanorods.This system which employs molecules like amylase can be successfully used for recognition of artificial latent fingerprints.The appropriate mechanism can be coupling of localized surface plasmon resonance in the nanorods mentioned above and the emission of Rhodamine 6G.As a result, we observe notable enhancement of the images of artificial latent fingerprints.
Keywords: Rhodamine 6G; Nanorod; Rhodamine; Forensic Fingerprint Detection Methods